Stability of Difference Schemes for Fractional Parabolic PDE with the Dirichlet-Neumann Conditions - Zafer Cakir (Abstract and Applied Analysis)
The stable difference schemes for the fractional parabolic equation with Dirichlet and Neumann boundary conditions are presented. Stability estimates and almost coercive stability estimates with ln (1/(𝜏+|ℎ|)) for the solution of these difference schemes are obtained. A procedure of modified Gauss elimination method is used for solving these difference schemes of one-dimensional fractional parabolic partial differential equations.